1995
DOI: 10.1002/joc.3370150106
|View full text |Cite
|
Sign up to set email alerts
|

Trends in wind and sea‐level pressure in the tropical pacific ocean for the period 1950–1979

Abstract: The COADS (Comprehensive Ocean-Atmosphere Data Set) sea-level pressure observations over the tropical Pacific Ocean during the period 195G-1979 are examined to check for dynamical consistency between the observed trends in wind-speed components and the trends in sea-level pressure pattern. There appears to be some evidence that the South east Pacific High and the equatorial trough in the central Pacific were gaining strength. As a result, trade winds appear to have been gaining strength along the northern flan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…The COADS pressure and wind observations have been found to be internally consistent in several other studies (e.g. Bunker, 1980;Woodruff et a/., 1987;Flohn and Kapala, 1989;Bigg, 1992;and Inoue and Bigg, 1993). Previous studies that examined a limited number of land pressure records (e.g.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The COADS pressure and wind observations have been found to be internally consistent in several other studies (e.g. Bunker, 1980;Woodruff et a/., 1987;Flohn and Kapala, 1989;Bigg, 1992;and Inoue and Bigg, 1993). Previous studies that examined a limited number of land pressure records (e.g.…”
Section: Resultssupporting
confidence: 79%
“…The shiprecorded data derives from the trimmed Comprehensive Ocean Atmosphere Data Set (COADS; Woodruff et ul., 1987), whiie the land-based station data comes from the Surface Station Climatology Data Set produced by the National Center for Atmospheric Research. Note that Inoue and Bigg (1993) showed that pressure trends present in both the raw COADS and trimmed data set are essentially identical.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other sources of observational error include: differences from nominal observing time; the anemometer type, calibration, and location; errors in calculation of true wind from the relative wind (Kent et al, 1993;Gulev, 1999;Smith et al, 1999); rounding artefacts; and for Beaufort winds, the stage of development of the waves. Researchers have studied the relationship between Voluntary Observing Ship (VOS) winds and pressures and have concluded that in some cases the pressure and wind trends are consistent (Inoue and Bigg, 1995) and in some cases inconsistent (Posmentier et al, 1989;Ward and Hoskins, 1996). It is important, therefore, to correct marine wind data to account for inhomogeneities for which we have correction techniques, such as for measurement height and atmospheric stability (Dobson, 1981;Smith, 1988;Walmsley, 1988) and for the Beaufort equivalent scale used to convert from observations of sea state to a wind speed (Lindau, 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…(2003) analyzed the wind data of northwestem Pacific and found that the wind field is related to Sonthem Oscillation Index (SOI), but has a half-year lag with respect to the SOL Besides the relationship between tropical Pacific wind fields and ENSO, the long-term variation of wind field has also been investigated. Inoue and Bigg (Inoue M, et al, 1995) analyzed COADS (Comprehensive OceanAtmosphere Data Set) sea-level pressure and wind observations and pointed out the trade winds gained strength over the eastedcentral equatorial Pacific during the period 195&1979. Clarke andLehedev(C1arkeA.…”
Section: Introductionmentioning
confidence: 99%